ENHANCING PHOTOVOLTAIC PERFORMANCE USING TITANIUM DIOXIDE BASED NANO-ENHANCED PCM FOR PASSIVE COOLING APPLICATIONS - Seto, Dewandono Bayu; Sudiro; Restu, Tuhu (LPPM Universitas Duta Bangsa Surakarta, 2025)
The performance of photovoltaic (PV) modules is significantly affected by the increase in operating temperature, which leads to reduced power output and overall efficiency. Therefore, passive cooling strategies are required to maintain stable energy conversion in solar systems. One widely investigated approach is the use of phase change materials (PCM) due to their ability to absorb and release latent heat, although their low thermal conductivity remains a major limitation. This study aims to evaluate the effectiveness of incorporating titanium dioxide nanoparticles into PCM, known as nano-enhanced PCM (NePCM), in improving the cooling performance of PV modules. The experimental method was conducted on a 50 Wp polycrystalline PV module under three conditions: without cooling, with pure PCM, and with titanium dioxide-based NePCM. The preparation of NePCM was carried out using a two-step method involving mechanical stirring and ultrasonic sonication to achieve a homogeneous nanoparticle dispersion. The results demonstrated that the addition of titanium dioxide improved the thermal conductivity of PCM, leading to lower operating temperatures, more stable voltage and power output, and higher energy conversion efficiency compared to both pure PCM and the uncontrolled condition. These findings highlight the potential of titanium dioxide-based NePCM as an effective, economical, and sustainable material for passive cooling applications in photovoltaic systems.